Potential use of red gypsum as glaze product - Syarifah Syazwani Syed Zulkiple (Penerbit Universiti Malaysia Perlis, 2011)
During the extraction process of titanium (iv) oxide from its ores, red gypsum were produced as the by-product. A total of 340,000 tonnes of red gypsum were produced per year in Malaysia. Main contents of red gypsum were CaO (36.6%), SO3 (35.8%), Fe2O3 (20.89%), TiO2 (4.61%) and small amount of Al2O3. Three most important components in making glaze are silica, flux and alumina. Red gypsum contain high flux in the form of more than 30% CaO and other oxide (10%) which is potential in making glaze for ceramics industry. In this study, material that contain alumina like feldspar, kaolin, bentonite as well as fly ash with high silica ( more than 60%) in the form of SiO were added to make a good glaze. Different composition of glaze were studied in term of its surface hardness, chemical resistance in acidic solution 10% HCl and 10 % KOH, as well as its impervious level. After the impervious test, no changes of color seen. In acid solution no staining observed. While in alkaline solution, the specimen showed a slightly gain weight and slightly staining on surface have been observed. For hardness test, scratching the specimen also gave the same result which was not visible. As a conclusion, red gypsum has the potential in production of glaze.